Marketing Strategy of the Samosir Lake Toba Regency Culture and Tourism Office in Increasing the Number of Tourists - Marpaung, Durahman; Tamba, Dang Panagaman (Dinasti Publisher, 2024)
The urgency of this research is that this research is important because it can provide an in-depth look at the strategies implemented by the Samosir Regency Culture and Tourism Office, so that concrete recommendations can be made to increase the attractiveness and popularity of these tourist destinations. This research aims to provide a deeper understanding of the challenges and opportunities faced by the Samosir Regency Culture and Tourism Office in expanding the number of tourists. The research methods used in this research are data collection obtained from observations, interviews with research subjects, and documentation studies, literature studies, identifying problems, preprocessing, analyzing data using SWOT analysis, BCG analysis, SPACE analysis, and QSPM analysis, data analysis results, final evaluation, research approach with mix method. The results of SWOT analysis on the evaluation of internal factors IFE and evaluation of external factors EFE show that the internal and external positions are in quadrant I, in a growing position and must continue to be improved. The results of the BCG matrix evaluation, Samosir Lake Toba Regency tourist destinations are classified in the Stars position. The results of the SPACE matrix calculation, the tourist position of Samosir Lake Toba Regency is in an aggressive position that occurs when all dimensions are positive. Based on the results of QSPM, 3 prioritized strategies can be taken and implemented as the main steps in developing tourist destinations.